Design for additive manufacturing : concepts and considerations for the aerospace industry - Bhate, Dhruv (SAE International, 2019)
When the earliest additive manufacturing (AM) technologies were developed in the 1980s and 1990s, their primary application was for the rapid manufacturing of prototypes. In the last decade, however, AM has rapidly emerged as a legitimate manufacturing process for a range of applications beyond prototyping, from tooling to end-use functional part production. Aerospace companies of all sizes have realized this earlier than most, and today, approximately 15% of all revenue generated in the AM industry can be traced back to aerospace applications [1]. There are a wide range of AM processes to choose from, broadly classified into six categories that between them span metals, polymers, ceramics, and biomaterials [2]. The one thing common to these technologies is a layered approach to building a part that uses an energy source such as light, heat, or an electron beam to convert a raw material such as a powder, filament, or resin into a part.
Keywords: Additive manufacturing.; Aerospace engineering.; Aerospace industries.; Technology assessment.; Composite materials.; Three-dimensional printing.; elektronické knihy; electronic books